ANALISIS EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI KACANG TANAH DI KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Felicia Marisa Sinabariba; Fembriarti Erry Prasmatiwi; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The study aims to indentify the factors that affect peanut’s farming, analyze the efficiency of using the production factors of peanut’s farming, and  calculate the farmers income of peanut’s farming in Central Lampung Regency. The research was conducted in Terbanggi Besar Subdistrict of Central Lampung Regency. The farmers respondents were chosen by simole random sampling. The collected data was analyzed by Cobb-Douglas production function, economic analysis by calculating the NPMxi/Pxi value, and farmer income analysis. The results showed that: the factors that affected the production of peanut farming were land area, seed, urea fertilizer and labor. The use of production factors were not efficient because the scale of peanut’s farming was in increasing return. The income earned by the farmers over the total cost was Rp2,747,846.72 with R/C ratio 2.00 and it was profitable.Key words : economic efficiency, income, peanut, production